1986
DOI: 10.1093/ageing/15.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality in an Initially Healthy Elderly Sample: Findings After Five Years of Follow-Up

Abstract: This report summarizes morbidity and mortality data for 263 initially healthy elderly men and women from the beginning of this study through five years of follow-up. The mortality rate for this sample averaged approximately 1.8% per year and the duration of terminal illness averaged 4.9 months. The cancer incidence rate has increased whereas new diagnoses of cardiovascular disease and degenerative conditions have declined. The data support the potential for maximizing vigour and health well into the seventh an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…This approximate rate of 5.7% per year is in keeping with the frequently quoted figures of around 5% per year for a population sample aged 65 years and over, especially as our sample represents an ageing cohort (e.g. Thomas et al, 1986;Murphy, 1983;Neilsen et al, 1977). Murphy (1983) in her one-year follow-up of depressive illness found that seven ( 1 9%) of her male patients and 10 ( I 1%) of her female patients were dead (combined rate of 14.1%), while Baldwin and Jolley (1986) found that eight (8.2%) of their sample of depressed patients were dead by one year.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This approximate rate of 5.7% per year is in keeping with the frequently quoted figures of around 5% per year for a population sample aged 65 years and over, especially as our sample represents an ageing cohort (e.g. Thomas et al, 1986;Murphy, 1983;Neilsen et al, 1977). Murphy (1983) in her one-year follow-up of depressive illness found that seven ( 1 9%) of her male patients and 10 ( I 1%) of her female patients were dead (combined rate of 14.1%), while Baldwin and Jolley (1986) found that eight (8.2%) of their sample of depressed patients were dead by one year.…”
Section: Discussionsupporting
confidence: 90%
“…In this we support the views of Thomas et al (1986) that prevention of premature morbidity can compress 'senescence'into a relatively short period at the end of a fixed lifespan. cooperation of the general practitioners and subjects involved.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Incidence data from large national health surveys are not available for all of the cardiovascular conditions occurring in this study. However, in a five‐year morbidity and mortality study of 263 initially healthy men and women (mean age, 72) conducted by Thomas et al, 29 18.6% of subjects were diagnosed as having some form of new‐onset heart disease by the end of the second year of the study. Of this group of subjects, 4.9% were noted to have ischemic heart disease; an additional 13.7% had other types of heart disease including cardiomegaly, congestive heart failure, aortic aneurysm, and problematic arrhythmias.…”
Section: Discussionmentioning
confidence: 97%
“…The mortality rate of both samples, in nursing homes and hospital wards, at 5 years was 69%, which is comparable to the 70% reported by Bond et a1 (1989), over a similar time period, from their comparable RCT of nursing homes and long-stay hospital wards for the elderly. Annual morality ratesforsamplesofelderlypeoplevaryintheliterature, from 5% upwards, depending on the sample type, age and setting, although they increase with older age (Murphy, 1983;Thomas et al, 1986;Davidson et al, 1988;Bond et al, 1989;Harwood and Ebrahim, 1991). Harwood and Ebrahim, for example, reported a mortality rate at 1 year for their samples of long-stay patients, with an average age of 84, of 44%, with no differences between type of wards.…”
Section: Discussionmentioning
confidence: 99%